Institutional logics in action - Lounsbury, Michael; Boxenbaum, Eva. (Bingley, U.K. : Emerald, 2013)
The institutional logics perspective is one of the fastest growing new theoretical areas in organization studies (Thornton, Ocasio & Lounsbury, 2012). Building on early efforts by Friedland & Alford (1991) to "bring society back in" to the study of organizational dynamics, this new scholarly domain has revived institutional analysis by embracing a focus on the dynamic and heterogeneous nature of institutions. In doing so, it has embraced a more practice-centered approach to agency that emphasizes situated interactions, the importance of history, the role of both symbolic and material elements, and the study of cross-level processes and mechanisms. This two volume set, seededby an ABC Network conference held in Banff, Alberta, CANADA in June 2012, provides a fresh set of papers by scholars at the cutting edge of research on institutional logics. As a whole, the papers provide many novel theoretical insights about institutional logics in actionfocusing on their dynamics, complexity, and evolving relationship to actors as actors actively navigate their social worlds.
Embedded in hybrid contexts : how individuals in organizations respond to competing institutional logics / Anne-Claire Pache, Filipe Santos -- Beyond the family firm : reasserting the influence of the family institutional logic across organizations / Samantha Fairclough, Evelyn R. Micelotta -- Putting new wine in old bottles : utilizing rhetorical history to overcome stigma associated with a previously dominant logic / Shilo Hills, Maxim Voronov, C.R. (Bob) Hinings -- Imageries of corporate social responsibility : visual recontextualization and field-level meaning / Markus A. Höllerer ... [et al.] -- Logic pluralism, organizational design, and practice adoption : the structural embeddedness of CSR programs / Mary Ann Glynn, Ryan Raffaelli -- Strange brew : bridging logics via institutional bricolage and the reconstitution of organizational identity / Lærke Højgaard Christiansen, Michael Lounsbury -- Instantiation of institutional logics : the "business case" for diversity and the prevalence of diversity mentoring practices / Shawna Vican, Kim Pernell-Gallagher -- The internal complexity of market logics : financial sophistication and price determination / Vince Feng -- Taking stock of institutional complexity : anchoring a pool of institutional logics into the interinstitutional system with a descendent hierarchical analysis / Thibault Daudigeos, Amélie Boutinot, Stéphane Jaumier.
Print version record
Keywords: Business & Economics -- Organizational Behavior; Business & Economics -- Organizational Development*.; Business & Economics -- Human Resources & Personnel Management; Organizational theory & behaviour; Management & management techniques; Organizational sociology; Associations, institutions, etc. -- Philosophy; Logic